2015
DOI: 10.1097/acm.0000000000000706
|View full text |Cite
|
Sign up to set email alerts
|

The Johns Hopkins Learning Environment Scale

Abstract: The JHLES is a new measure to assess students' perceptions of the medical school LE, with supporting validity evidence and content describing the social, relational, and academic processes of medical school that support students' professional formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
49
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 23 publications
4
49
1
3
Order By: Relevance
“…Each item is scored 1‐5 so that JHLES totals can range from 28 to 140, with higher scores indicating a more positive perception of the learning environment. Validity evidence for content, response process, internal structure and relationship to other variables has been described in previous studies …”
Section: Methodssupporting
confidence: 52%
See 3 more Smart Citations
“…Each item is scored 1‐5 so that JHLES totals can range from 28 to 140, with higher scores indicating a more positive perception of the learning environment. Validity evidence for content, response process, internal structure and relationship to other variables has been described in previous studies …”
Section: Methodssupporting
confidence: 52%
“…Perception of the learning environment was assessed using the Johns Hopkins Learning Environment Scale (JHLES). The JHLES was developed over a series of steps from 2010 to 2012 at Johns Hopkins University School of Medicine . It has 28 items, each with five‐point response options.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 The learning environment influences students' professional and identity development, and studies have found that optimized learning environments have positive impacts on humanism, achievement and student learning. 2,3 At the same time, a poor learning environment has been shown to be associated with increased student burnout and distress.…”
mentioning
confidence: 99%